Aberrant DNA Methylation At HOXA4 And HOXA5 Genes Are Associated With Resistance To Imatinib Mesylate Among Chronic Myeloid Leukemia Patients - Marjanu Hikmah Elias; Husin Azlan; Sarina Sulong; Abdul Aziz Baba; Ravindran Ankathil (WILEY, 2024)
Indexed by SCOPUS